An Assessment of the Functioning of Shopping Centres in Central‑Eastern Europe on the Example of "Posnania Mall" in Poznań (Poland) and "Grand Mall" in Varna (Bulgaria) - Palicki, Sławomir; Stoyanov, Stoyan; Kostov, Ivo; Atanasova, Tsvetelina; Ostrowski, Patrycjusz (Geomatics and Environmental Engineering, 2021)
The article explores the issue of the function of shopping centres, in particular the analysis of the impact of their presence on society and the local development of cities and regions. Regarding the empirical aspect, the examples of Poznań (Poland) and Varna (Bulgaria) will be presented. As a result of similar socio‑economic conditions and joining the European Union at almost the same moment, all comparative studies reflecting preferences and market reactions seem both viable and interesting. In addition, the two cities chosen for the studies occupy a similar place in the hierarchy of the settlement network in their countries. They are large, well‑developed centres that attract the attention of investors from various segments of the real estate market. The research is part of the modelling of preferences of shopping centre customers areas, which in particular supports the investment decisions of developers operating in the analysed real estate market, and at the same time permits a diagnosis of social satisfaction. A derivative of the research is also the reconstruction of the effects of the functioning of large‑scale shopping malls in two Central‑Eastern European countries.